Thiopental-Dexmedetomidine as Adjuvant Anesthesia for Craniotomy Tumor Removal: A Case Report - Bisri, Dewi Yulianti; Nuryanda, Dian; Alifahna, Muhammad Rezanda; Bisri, Tatang (Jurnal Neuroanestesi Indonesia, 2024)
Brain tumor surgery requires special anesthesia to get a slack brain and perform perioperative brain protection. The selected anesthetic drugs and adjuvants have the ability of anesthesia sparring effect and have a brain protective effect. Not many have done the combination of thiopental adjuvant with dexmedetomidine. The purpose of this case report is to see the effect of the combination of thiopental with dexmedetomidine as an adjuvant anesthesia on hemodynamics and slack brain and successful removal of brain tumors. A woman, 32 years old, with meningiomas had surgery to remove a brain tumor at Santosa Bandung Central Hospital. Preoperative examination showed blood lab results within normal limits, the presence of large meningioma and midline shift. Induction of anesthesia with thiopental 5 mg/kgBW, rocuronium bromide 0.9 mg/kgBW, fentanyl 3 mcg/kg and anesthetic maintenance with sevoflurane below 1.5 MAC, oxygen/air, continuous rocuronium 0.5 mg/kgBW/hour, thiopental and continuous dexmedetomidine. The anesthetic adjuvant used was thiopental 1-3 mg/kg/hour and continuous dexmedetomidine 0.40.7 mcg/kg/hour. A slack brain is obtained, and 90% of the tumor could be removed, and transfused during surgery 4 units pack red cells (PRC), crystalloid liquid as much as 2,500 cc, and colloidal fluid as much as 2,000 cc. The length of surgery is 11 hours. Post-surgery was treated in the ICU for 5 days, then moved to the ward for 2 days then the patient could be discharged from the hospital. The use of thiopental and dexmedetomidine continuously can produce slack brain and almost the entire tumor can be removed.